Pengembangan Aplikasi CIKUR Untuk Mengidentifikasi Blind Code Tactile Effect Terhadap Penyandang Disabilitas Tunanetra di SLB Pembina Sulawesi Selatan - Moghina Fahmi; Zulhajji, Zulhajji; Jumadi Mabe Parenreng (Jurusan Teknik Informatika dan Komputer, 2020)
This research is a research and development (Research and Development) with a prototype development model. The research objective is the development of the CIKUR application for blind students, knowing the appropriateness of the application, and knowing the user's response to the application development. Research data obtained from interviews, observations, and questionnaires by respondents. Application test results are obtained by analyzing aspects of functionality and usability based on ISO 25010 standards. The results of the CIKUR application development are in the form of two main components namely the scan menu and the about menu. From the results of testing the functionality obtained eligibility of applications with a percentage of 100% with a category acceptable. The usability test results obtained a percentage of 90% with a frequency of 18 and included in the category of strongly agree. Then the percentage of 10% with a frequency of 2 and included in the agreed category